The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1108/jpif-06-2014-0043
|View full text |Cite
|
Sign up to set email alerts
|

Real estate fund active management

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link: Abstract:The traditional way to measure the active management of a fund is to calculate its tracking error: as measured by the standard deviation of the difference in a fund's returns versus its benchmark returns. However, tracking error alone is an inadequate measure of fund activity since even very actively managed funds can in fact generate rather low tracking er… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(91 reference statements)
1
3
0
Order By: Relevance
“…For example, Jiang et al (2014) find that overweighted positions in funds relative to their benchmarks have outperformed their underweighted positions, showing the shrinking fraction of assets managed by activefund managers. Muller and Weber (2012), Lee and Morri (2015), and Frijns and Indriawan (2018) are recent papers confirming that previous results for US mutual funds hold in other markets, such as New Zealand and Europe.…”
Section: Introductionsupporting
confidence: 82%
“…For example, Jiang et al (2014) find that overweighted positions in funds relative to their benchmarks have outperformed their underweighted positions, showing the shrinking fraction of assets managed by activefund managers. Muller and Weber (2012), Lee and Morri (2015), and Frijns and Indriawan (2018) are recent papers confirming that previous results for US mutual funds hold in other markets, such as New Zealand and Europe.…”
Section: Introductionsupporting
confidence: 82%
“…Source: Own presentation With a total of 15 out of 20, an equal number of participating firms were real estate investors or investment managers active in the core-plus investment area. Core-plus properties resemble core properties in many ways, but they require a certain degree of active management (Lee & Morri, 2015). For instance, an office property might be located in the Central Business District (CBD) in Frankfurt but has vacant areas.…”
Section: Description Of the Set Of Participantsmentioning
confidence: 99%
“…Seventeen firms indicated that they were active in the value-add investment segment. Valueadd investors conduct active asset management to a higher degree than core-plus investors, for instance, by refurbishing or reconstructing a property (Lee & Morri, 2015). Thus, valueadd investors add value to their investments.…”
Section: Description Of the Set Of Participantsmentioning
confidence: 99%
See 1 more Smart Citation